2016
DOI: 10.1139/cjc-2016-0290
|View full text |Cite
|
Sign up to set email alerts
|

The INV24 test set: how well do quantum-chemical methods describe inversion and racemization barriers?

Abstract: For years, there has been ongoing interest in experimentally and theoretically understanding inversion and racemization processes. However, to the best of our knowledge, there has been no computational study that systematically investigated how well low-level quantum-chemical methods predict inversion barriers. Herein, we provide an answer to this question and we present the INV24 benchmark set of 24 high-level, ab initio inversion barriers. INV24 covers inversion in triatomics, in pyramidal molecules, in one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 126 publications
2
39
0
Order By: Relevance
“…In 2016, Goerigk and Sharma presented the first comprehensive benchmark set for BHs in inversion and racemisation reactions (INV24). 84 It comprises 24 BHs for inversion in triatomic, pyramidal, cyclic, helical and bowl-shaped systems calculated at the W2-F12, W1-F12 or DLPNO-CCSD(T)/TightPNO/CBS(def2-TZVPP/def2-QZVPP) levels of theory ranging from 4.5 to 79.7 kcal mol À1 . The average barrier is 31.85 kcal mol À1 .…”
Section: 32mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Goerigk and Sharma presented the first comprehensive benchmark set for BHs in inversion and racemisation reactions (INV24). 84 It comprises 24 BHs for inversion in triatomic, pyramidal, cyclic, helical and bowl-shaped systems calculated at the W2-F12, W1-F12 or DLPNO-CCSD(T)/TightPNO/CBS(def2-TZVPP/def2-QZVPP) levels of theory ranging from 4.5 to 79.7 kcal mol À1 . The average barrier is 31.85 kcal mol À1 .…”
Section: 32mentioning
confidence: 99%
“…An exception to this rule are DFAs that contain a nonlocal vdW kernel, such as VV10 or oB97X-V. 153,155 Over the past years, it has been demonstrated that dispersion corrections also positively influence geometries of organic and biomolecular systems 44,[223][224][225][226][227][228] as well as the description of reaction energies and BHs. 50,84,222,229 This topic was also discussed for GMTKN30 in 2011. 7 These are only some of many examples in the literature, and yet, we still observe the common trend to rely on uncorrected DFAs in many computational organic chemistry applications; for a discussion on the shortcomings of such an approach, see e.g.…”
Section: The Need For Dispersion Correctionsmentioning
confidence: 99%
“…In fact, it influences structural features of molecules and crystals, thermochemical properties, and reaction mechanisms. [40,68,74,[127][128][129][130][131][132][133][134][135] Bulky chemical groups can even serve as 'dispersion energy donors' [128] to overcome steric repulsion to form novel molecular structures. [127] When paired with a robust DFA, modern dispersion-corrected DFT has unprecedented accuracy and even outperforms some ab initio wave-function methods, as we demonstrated in our largest DFT benchmark study ever published.…”
Section: Long-range Interactions Treated By the Dispersion Correctionmentioning
confidence: 99%
“…[12][13][14] DHDFAs are currently regarded as the most sophisticated and most accurate DFAs for molecular thermochemistry, surpassing popular wave-function approaches, such as Møller-Plesset perturbation theory or even the composite complete-basis-set (CBS-QB3) approach. 8,[15][16][17][18][19] Due to its success for electronic ground states, the DHDFA approach has also been extended to the computation of electronic excitation energies. A first solution suggested by Grimme and Neese was to transfer the configuration interaction singles with perturbative doubles 20 (CIS(D)) approach to a time-dependent DFT (TD-DFT) formalism in 2007 (TD-DHDFAs).…”
mentioning
confidence: 99%